Conservation process and significance. A methodological approach to plan shelters in archaeological sites - Cesare Sposito; Francesca Scalisi (Agathón)
Within the scientific debate on the conservation of Cultural Heritage in general and Archaeological Heritage in particular, due to its twofold nature (material and immaterial) and consistently with the interest taken by Technological Culture in the importance of those aspects in the process crucial for their proper development and broad enjoyment, this paper proposes an evaluation model to understand ‘what’ to preserve and ‘why’ for a sustainable development, even before considering ‘how’ to do so, allowing a clearer reading and an easier interpretation of the complex relationships existing between the archaeological pre-existences, the natural environments and the added anthropic systems. The offered evaluation model can guide operators towards conscious sheltering planning with architectural value, promoting the identification of the morphological, typological and technical-constructive solutions most suitable to return the potential significance of the Asset.